Evaluation of nutritional status of young adolescents diagnosed with Down syndrome: a descriptive study - Kahraman, Sevde; Karsli, Eslem; Ihlamur, Murat (SPRINGERNATURE, 2024)
PurposeDown syndrome (DS) is the most common chromosomal disorder causing health problems such as obesity and constipation. It is important for adolescents with DS, who are still growing and developing, to adopt healthy eating habits. The aim of this study is to evaluate the anthropometric and nutritional status of young adolescents with DS.MethodsThis study was conducted on 90 young adolescents, aged 9-13 years, with DS who were receiving services at special education centers referred by the Down Syndrome Association in Istanbul. During the study period, data were collected using the Sociodemographic and General Health Information Form, 3-Day Food Consumption Record, and Food Consumption Frequency Form.ResultsAmong the young adolescents with DS who participated in the study, 26.6% were overweight and 44.4% were obese patients. According to the 3-day food records of the adolescents, the average daily energy intake was 1639 +/- 514.1 kcal. When evaluated according to the recommended daily energy intake, it was found that 51.2% had an insufficient energy intake and 5.6% had an excess energy intake.ConclusionAlthough the incidence of obesity is high in young adolescents with DS, it is seen that there is inadequate energy intake. Because of this variable situation, adolescents with DS must be individually evaluated, receive medical nutrition therapy, and be followed up.
Keywords: Down syndrome; Adolescents; Nutritional status; OBSTRUCTIVE SLEEP-APNEA; CHILDREN; PREVALENCE; OVERWEIGHT; OBESITY; Food Science & Technology; Nutrition & Dietetics